Estudio arqueológico del sitio El Morro: un puerto prehispánico en la costa del Pacifico nor-ecuatorial (departamento de Nariño, Colombia) - Bouchard, Jean François (Revista Española de Antropología Americana, 2003)
The archaeological research in El Morro site (Tumaco, Colombia) brought to light two prehispanic occupations. The first one belongs to Tumaco-La Tolita cultural phase. The second one, properly el Morro, more recent (between 4th and 5th centuries AD) with a very different pottery, is considered an occupation by fishermen and/or maritime traders.
Keywords: Archaeology; Tumaco; La Tolita; Ecuador; Colombia